How does emergency remote teaching affect EFL students’ writing skills? - Liqaa Habeb Al-Obaydi; Farzaneh Shakki; Marcel Pikhart (Cogent Education)
Writing is among the most challenging language skills, and it necessitates memorization and practice. Nevertheless, there has been an increasing interest in research on the difficulties the learners encounter and the solutions to enhance the learners’ writing skills. This study aims to scrutinize the mistakes that English Foreign Language (EFL) learners make in their writing, the challenges that arise from their heavy reliance on Emergency Remote Teaching (ERT), and also the potential solutions and suggestions for improving their writing skills. To collect the data, teacher interviews were done in addition to document analysis using a sample of written texts. Written samples of student paper-sheet data were statistically analyzed using frequency and percentage, while teacher interviews from two countries, namely Iraq and the Czech Republic, were evaluated subjectively. The findings show that both groups agreed that writing proficiency is a controversial issue and that it is a skill that is ignored in online courses. It further shows that Czech EFL learners display a lack of grammar, while Iraqi EFL learners show a noticeable shortage in spelling and punctuation.